2001
DOI: 10.1108/09590550110405321
|View full text |Cite
|
Sign up to set email alerts
|

Using a behavior‐based method to identify and reduce employee theft

Abstract: The consequences of employee theft have a profound impact on employers, employees, consumers, and society. Estimates of employee theft range from $40 to $400 billion a year in the USA alone. Although identifying employee theft is difficult, certain behavioral‐based studies have been able to separate employee theft from customer theft (shoplifting). The current study extends a behavioral‐based technique (posting) by posting total monetary loss and total items missing rather than posting the individual targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Experts believe, however, that the results in this study might be low because the National Service Security Council gathered this data from self-reports (Kidwell & Kochanowski, 2005). Oliphant and Oliphant (2001) indicated that several studies have attempted to identify an employee theft base rate; however, the results produced a wide range from 3% to 62%. These wide range rates were also obtained from sensitive self-report information; therefore, the results may remain inaccurate.…”
Section: Business Response To Employee Theftmentioning
confidence: 87%
See 3 more Smart Citations
“…Experts believe, however, that the results in this study might be low because the National Service Security Council gathered this data from self-reports (Kidwell & Kochanowski, 2005). Oliphant and Oliphant (2001) indicated that several studies have attempted to identify an employee theft base rate; however, the results produced a wide range from 3% to 62%. These wide range rates were also obtained from sensitive self-report information; therefore, the results may remain inaccurate.…”
Section: Business Response To Employee Theftmentioning
confidence: 87%
“…Unfortunately, the literature indicated that the majority of employee theft is not discovered. The data suggested that only very few employees are ever caught stealing, and it is estimated that as much as 80% of employee theft goes undetected (Oliphant & Oliphant, 2001). Additionally, there are more factors contributing to inventory loss that businesses need to consider.…”
Section: Business Response To Employee Theftmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been long known that shrinkage is frequently attributed to the wrong cause (Bernstein, 1963). For example, retailers often emphasise external theft as a cause of shrinkage as they are in denial of the level of theft by their own employees and therefore retailers underreport internal theft (Oliphant and Oliphant, 2001).…”
Section: Shrinkagementioning
confidence: 99%